Selective Optical Chemical Sensing of Ferrous (Fe2+) and Cupric (Cu2+) Ions by Pyridine Based Sulfonamide - Batool, Madeeha; Khan, Iqra Saleem; Farooq, Muhammad Umar; Jalees, Muhammad Irfan; Solangi, Amber Rehana; Qadir, Muhammad Abdul; Alizadeh, Javad; Taher, Mohammad Ali (Topics in catalysis, 2025)
Sulfonamides and their derivatives are being used as potent chemosensors for various ions. Sensing ability of 4-methyl-N-(pyridin-2-yl) benzene-1-sulfonamide (S) was tested towards different cations i.e. Zn 2+ , Fe 2+ , Pb 2+ , Ni 2+ , Sr 2+ , Cd 2+ , Cu 2+ , Co 2+ , Hg 2+ and Al 3+ in Dimethyl Sulfoxide (DMSO). S exhibited sensitivity towards ferrous (Fe 2+ ) and cupric (Cu 2+ ) ions. Solution of S turned yellow from colorless upon interaction with iron and copper ions and a corresponding bathochromic shift was observed. Electronic spectra showed new absorbance peaks at 310 nm and 370 nm after interaction with Fe 2+ and Cu 2+ respectively, compared with S absorbance peak at 270 nm. Binding studies indicated 1:1 binding stoichiometry of both metal ions with S. Detection limits for iron and copper were determined to be 0.74 µM and 0.60 µM, respectively. However, their binding constant values came out to be 1.3 × 10 6 M −1 and 1 × 10 6 M −1 respectively for Fe 2+ and Cu 2+ .